(untitled) (Modern education and development, 2025)
The integration of artificial intelligence (AI) into database management and design has significantly enhanced the efficiency and accuracy of data organization, analysis, and storage. This article presents an algorithm for forming databases using AI techniques, focusing on machine learning, clustering, and data mining methods. The proposed algorithm automates the process of structuring and managing large datasets, improving the decision-making capabilities of database systems. By employing AI models, such as neural networks and support vector machines, the algorithm adapts to evolving data patterns and ensures optimal organization of information. This work explores the underlying AI principles used in database formation, highlights the key benefits, and outlines challenges in applying these technologies to real-world database systems.